Pengaruh Mitos dan Realiti Terhadap Pembentukan Identiti Masyarakat Jawa: The Influence of Myth and Reality on The Formation of Javanese Community Identity - Kamis, Mariyah Jamilah; Hashim Ismail ,; Eizah Mat Hussain , (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2025)
This study explores the relationship between myth and reality in the context of historical and sacred sites in Java, Indonesia, and how these belief narratives shape the cultural and social identity of local communities. As a center of traditional culture, Java has long been a meeting point of mythological elements and historical facts rooted in Hindu, Buddhist, Islamic, and colonial influences. Sites such as Mount Merapi, and Prambanan Temple, are not only recognized for their geographical or historical significance but are also mythologized with stories of sacredness, supernatural beings, and symbols of power. Using a qualitative approach through document analysis and literature review, this research aims to understand how myth is embedded in physical and social spaces, functioning as a tool for socialization, moral education, and the preservation of social structures. Findings reveal that myth and reality are not separate entities but rather support and reflect the cultural values of Javanese society. Myths surrounding sacred places help strengthen local identity, maintain social stability, and assign symbolic meaning to the physical environment. Furthermore, these mythic narratives are continuously recycled through performing arts, religious rituals, and popular media, making them a vital element in contemporary cultural discourse. This study contributes to a deeper understanding of the role of mythic narratives in the cultural and historical landscape of modern Java.